The effect of the ventilation retrofit in a school on CO2, airborne particles, and energy consumptions. (June 2019) - Stabile, L.; Buonanno, G.; Frattolillo, A.; Dell'Isola, M.
Abstract: The energy retrofit of existing buildings is a key strategy to reduce the energy costs of the building sector. Amongst the retrofit solutions, the adoption of mechanical ventilation systems represents a necessary approach for buildings with high crowding index, such as schools. The air quality in schools is a main issue since children spend a significant fraction of the year in such microenvironments. To date, the scientific literature has carried out several studies concerning the air quality in naturally ventilated schools worldwide, nonetheless most of the studies performed a general evaluation of the air quality just using the CO2 as a comprehensive indicator. This is an oversimplified approach since the indoor air quality is affected by several pollutants, including airborne particles, whose behavior cannot be predicted by the CO2 one. The aim of the research is the evaluation of the effect of the ventilation retrofit in a classroom on different indoor air quality parameters and energy consumption. To this end a mechanical ventilation system with a heat recovery unit was installed in a test-classroom and tests with CO2 -based demand controlled ventilation were performed. CO2 levels and indoor-to-outdoor particle concentrations were measured and compared to the pre-retrofit ventilation conditions (i.e. manual airing procedures). Results showed that mechanical ventilation systems have simultaneous positive effects on the different pollutants investigated as well as on ventilation heat losses: indeed, lower indoor-to-outdoor concentration ratios, with respect to the airing approach, were detected simultaneously for CO2, sub-micron particles and PM10 . Highlights: Indoor air quality and energy need in a classroom pre-/post-ventilation retrofit. Indoor and outdoor measurements of CO2, particle number and PM10 concentrations. Application of a mechanical ventilation system with energy recovery unit. Improvement of indoor air quality and energy need with the post-retrofit solution. Energy saving of 32% of the post-retrofit solution with respect the manual airing.